La sociedad del conocimiento: cantidad, categoría y género de los investigadores en Ecuador - Zambrano Mendoza, Jose Luis (2020)
Science and the development of technologies is the key for the economic progress of any country, and at the same time, a determining factor in the construction of more sustainable and responsible societies for the conservation and management of natural resources. A fundamental agent in science is the scientist. This study investigates the amount, category and gender of researchers that Ecuador has in the different areas of knowledge, and carries out an analysis of the existing policies to promote the researcher's career. It was observed that, in spite of the mechanisms designed to increase the quantity, the lack of clarity and application of regulations prevents the incorporation of more researchers, which could delay the economic and productive development of the country.